Acquired Idiopathic Stiffness After Total Knee Arthroplasty: A Systematic Review and Meta-Analysis - Tibbo, Meagan E. (J Bone Joint Surg Am, 2019)
BACKGROUND: Stiffness is a common reason for suboptimal clinical outcomes after primary total knee arthroplasty (pTKA). There is a lack of consensus regarding its definition, which is often conflated with its histopathologic subcategory—i.e., arthrofibrosis. There is value in refining the definition of acquired idiopathic stiffness in an effort to select for patients with arthrofibrosis. We conducted a systematic review and meta-analysis to establish a consensus definition of acquired idiopathic stiffness, determine its prevalence after pTKA, and identify potential risk factors for its development. METHODS: MEDLINE, Embase, Cochrane Controlled Register of Trials (CENTRAL), and Scopus databases were searched from 2002 to 2017. Studies that included patients with stiffness after pTKA were screened with strict inclusion and exclusion criteria to isolate the subset of patients with acquired idiopathic stiffness unrelated to known extrinsic or surgical causes. Three authors independently assessed study eligibility and risk of bias and collected data. Outcomes of interest were then analyzed according to age, sex, and body mass index (BMI). RESULTS: In the 35 included studies (48,873 pTKAs), the mean patient age was 66 years. In 63% of the studies, stiffness was defined as a range of motion of <90° or a flexion contracture of >5° at 6 to 12 weeks postoperatively. The prevalence of acquired idiopathic stiffness after pTKA was 4%, and this did not differ according to age (4%, I(2) = 95%, among patients <65 years old and 5%, I(2) = 96%, among those ≥65 years old; p = 0.238). The prevalence of acquired idiopathic stiffness was significantly lower in males (1%, I(2) = 85%) than females (3%, I(2) = 95%) (p < 0.0001) as well as in patients with a BMI of <30 kg/m(2) (2%, I(2) = 94%) compared with those with a BMI of ≥30 kg/m(2) (5%, I(2) = 97%) (p = 0.027). CONCLUSIONS: Contemporary literature supports the following definition for acquired idiopathic stiffness: a range of motion of <90° persisting for >12 weeks after pTKA in patients in the absence of complicating factors including preexisting stiffness. The mean prevalence of acquired idiopathic stiffness after pTKA was 4%; females and obese patients were at increased risk. LEVEL OF EVIDENCE: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.